Genetic Manipulation of sn-1-Diacylglycerol Lipase and CB1 Cannabinoid Receptor Gain-of-Function Uncover Neuronal 2-Linoleoyl Glycerol Signaling in Drosophila melanogaster. - Tortoriello, G.; Beiersdorf, J.; Romani, S.; Williams, G.; Cameron, G.A.; Mackie, K.; Williams, M.J.; Di Marzo, V.; Keimpema, E.; Doherty, P.; Harkany, T. (Cannabis and cannabinoid research, 2021)
Introduction: In mammals, sn-1-diacylglycerol lipases (DAGL) generate 2-arachidonoylglycerol (2-AG) that, as the major endocannabinoid, modulates synaptic neurotransmission by acting on CB1 cannabinoid receptors (CB1R). Even though the insect genome codes for inaE, which is a DAGL ortholog (dDAGL), its products and their functions remain unknown particularly because insects lack chordate-type cannabinoid receptors. Materials and Methods: Gain-of-function and loss-of-function genetic manipulations were carried out in Drosophila melanogaster, including the generation of both dDAGL-deficient and mammalian CB1R-overexpressing flies. Neuroanatomy, dietary manipulations coupled with targeted mass spectrometry determination of arachidonic acid and 2-linoleoyl glycerol (2-LG) production, behavioral assays, and signal transduction profiling for Akt and Erk kinases were employed. Findings from Drosophilae were validated by a CB1R-binding assay for 2-LG in mammalian cortical homogenates with functionality confirmed in neurons using high-throughput real-time imaging in vitro. Results: In this study, we show that dDAGL is primarily expressed in the brain and nerve cord of Drosophila during larval development and in adult with 2-LG being its chief product as defined by dietary precursor availability. Overexpression of the human CB1R in the ventral nerve cord compromised the mobility of adult Drosophilae. The causality of 2-LG signaling to CB1R-induced behavioral impairments was shown by inaE inactivation normalizing defunct motor coordination. The 2-LG-induced activation of transgenic CB1Rs affected both Akt and Erk kinase cascades by paradoxical signaling. Data from Drosophila models were substantiated by showing 2-LG-mediated displacement of [3H]CP 55,940 in mouse cortical homogenates and reduced neurite extension and growth cone collapsing responses in cultured mouse neurons. Conclusions: Overall, these results suggest that 2-LG is an endocannabinoid-like signal lipid produced by dDAGL in Drosophila.